The Effect of Glucocorticoid and Glucocorticoid Receptor Interactions on Brain, Spinal Cord, and Glial Cell Plasticity. (8th August 2017) - Madalena, Kathryn M.; Lerch, Jessica K.
Abstract : Stress, injury, and disease trigger glucocorticoid (GC) elevation. Elevated GCs bind to the ubiquitously expressed glucocorticoid receptor (GR). While GRs are in every cell in the nervous system, the expression level varies, suggesting that diverse cell types react differently to GR activation. Stress/GCs induce structural plasticity in neurons, Schwann cells, microglia, oligodendrocytes, and astrocytes as well as affect neurotransmission by changing the release and reuptake of glutamate. While general nervous system plasticity is essential for adaptation and learning and memory, stress-induced plasticity is often maladaptive and contributes to neuropsychiatric disorders and neuropathic pain. In this brief review, we describe the evidence that stress/GCs activate GR to promote cell type-specific changes in cellular plasticity throughout the nervous system.